Penerapan Algoritma Advanced Encryption Standard (AES) Untuk Keamanan Data Transaksi Pada Sistem E-Marketplace - Muhammad Riyan Andriyanto; Pristi Sukmasetya (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Sriwedari Village known as a producer of superior plant seeds and fruits in the Salaman District area. The Sriwedari Seed Shop is a form of business from the village government that sells various kinds of plant seeds and fruits from nurseries by the local community. However, in its application the sales and transaction system still uses a fairly conventional method. By opening an offline store and marketing products through social media networks, the Sriwedari Seed Shop has less regular customers. Not to mention the risk of fraud from customers who order seeds through social media is a concern for sellers Therefore, this research was conducted with the intention of answering the problems above by creating an e-marketplace system in the form of an online store that will be integrated with a payment gateway that has various online payment methods. In addition, data security will also be applied to the payment system using the Advanced Encryption Standard (AES) cryptographic algorithm which functions to encrypt payment transaction data so that data records stored in the database are not easy to read and prevent misuse of data by parties who do not have access rights. The method used in developing this system is Rapid Application Development (RAD). This method is very suitable to be applied in software development with minimal resources so that it can speed up the iteration process at each stage of development while still paying attention to input from potential system users. The results of this research are an integrated e-marketplace system with payment gateway services that have various payment methods with transaction data security using the AES cryptographic algorithm.